Transverse and Impact Strength of Poly Methyl Methacrylate-Zirconium Oxide Nanocomposite Denture Base Material - Yazan Hussam Al-D; Ammar Khalid Al-Noori (University of Mosul, College of Dentistry, 2023)
Aims: this study aims to evaluate the effect of adding two concentrations of zirconium oxide nanoparticles (1.0% and 2.0%) to "heat-cured PMMA" in order to improve its mechanical properties such as transverse strength and impact strength. Materials and Methods: The particle size of Zirconium Oxide ZrO2 was 20nm. The ZrO2 nanoparticles were added to the "heat-cured PMMA" resin base at 1.0% and 2.0% by weight, respectively, to create a PMMA-ZrO2 nanocomposite with two various percentages compared to PMMA without additives. For the transverse strength and impact strength tests, the traditional heat-curing technique was cured with a water bath to polymerize the specimens. The results of the study were statistically analyzed by using one-way ANOVA and Duncan's multiple range test with a significant P-value of 0.05. Results: The results showed that there was an increase in the transversal and impact strength for the PMMA-ZrO2 nanocomposite at concentrations of 1.0% and 2.0% respectively, after comparison of the findings at 0.05. Conclusions: The use of Zirconium Oxide nanoparticles as dental fillers at 1% and 2% by weight improved the transverse strength and impact strength of PMMA denture base material.